Global Outcome Trajectories up to 10 Years After Moderate to Severe Traumatic Brain Injury - Forslund, Marit V.; Perrin, Paul B.; Røe, Cecilie; Sigurdardottir, Solrun; Hellstrøm, Torgeir; Berntsen, Svein A.; Lu, Juan; Arango-Lasprilla, Juan Carlos; Andelic, Nada (Frontiers in Neurology, 2019)
Aims: Based on important predictors, global functional outcome after traumatic brain injury (TBI) may vary significantly over time. This study sought to: 1) describe changes in the Glasgow Outcome Scale–Extended (GOSE) score in survivors of moderate to severe TBI, 2) examine longitudinal GOSE trajectories up to 10 years after injury, and 3) investigate predictors of these trajectories based on socio-demographic and injury characteristics. Methods: Socio-demographic and injury characteristics of 97 TBI survivors aged 16–55 years were recorded at baseline. GOSE was used as a measure of TBI-related global outcome and assessed at 1-, 2-, 5-, and 10-year follow-ups. Hierarchical linear models were used to examine global outcomes over time and whether those outcomes could be predicted by: time, time*time, sex, age, partner relationship status, education, employment pre-injury, occupation, cause of injury, acute Glasgow Coma Scale score, length of post-traumatic amnesia (PTA), CT findings, and Injury Severity Score (ISS), as well as the interactions between each of the significant predictors and time*time. Results: Between 5- and 10-year follow-ups, 37% had deteriorated, 7% had improved, and 56% showed no change in global outcome. Better GOSE trajectories were predicted by male gender (p = 0.013), younger age (p = 0.012), employment at admission (p = 0.012), white collar occupation (p = 0.014), and shorter PTA length (p = 0.001). The time*time*occupation type interaction effect (p = 0.001) identified different trajectory slopes between survivors in white and blue collar occupations. The time*time*PTA interaction effect (p = 0.023) identified a more dramatic increase and subsequent decrease in functional level among survivors with longer PTA duration. Conclusion: A larger proportion of survivors experienced deterioration in GOSE scores over time, supporting the concept of TBI as a chronic health condition. Younger age, pre-injury employment, and shorter PTA duration are important prognostic factors for better long-term global outcomes, supporting the existing literature, whereas male gender and white collar occupation are vaguer as prognostic factors. This information suggests that more intensive and tailored rehabilitation programs may be required to counteract a negative global outcome development in survivors with predicted worse outcome and to meet their long-term changing needs.